2012
DOI: 10.1186/1471-2342-12-3
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel enteroclysis with magnetic resonance imaging and computed tomography in patients with failed and uncertain passage of a patency capsule

Abstract: BackgroundVideo capsule enteroscopy (VCE) has revolutionized small bowel imaging, enabling visual examination of the mucosa of the entire small bowel, while MR enteroclysis (MRE) and CT enteroclysis (CTE) have largely replaced conventional barium enteroclysis. A new indication for MRE and CTE is the clinical suspicion of small bowel strictures, as indicated by delayed or non-delivery of a test capsule given before a VCE examination, to exclude stenosis. The aim of this study was to determine the clinical value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Alternatives are arguably less desirable: our study suggests that radiologists would request abdominal CT anyway for most patients after reviewing the plain abdominal film, which remains common practice. Other alternatives are likely to be more complicated: a recent study by Fork et al . recommended magnetic resonance enteroclysis (MRE) and CT enteroclysis (CTE) as alternative methods of ensuring safe passage of CE in the subgroup of patients who had an initial PC test with a late or unconfirmed excretion of the capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatives are arguably less desirable: our study suggests that radiologists would request abdominal CT anyway for most patients after reviewing the plain abdominal film, which remains common practice. Other alternatives are likely to be more complicated: a recent study by Fork et al . recommended magnetic resonance enteroclysis (MRE) and CT enteroclysis (CTE) as alternative methods of ensuring safe passage of CE in the subgroup of patients who had an initial PC test with a late or unconfirmed excretion of the capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inflammatory lesions might exist outside the reachable range of the colonoscope. Because one of the major limitations of capsule endoscopy is capsule retention, this procedure cannot be undergone by patients with severe stenosis or with failed and uncertain passage of a patency capsule [12]. It is difficult to observe the entire small intestine by balloon endoscopy, and the patient requires conscious sedation during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…However, experience with patency capsules has been disappointing, with many patients reporting delayed or nonpassage of the patency capsule [11]. A recent study has shown that CT or MR enterography is sufficient for the investigation of most patients with small bowel disease and VCE can be used as a subsequent investigation if necessary [12]. …”
Section: Discussionmentioning
confidence: 99%